2003
DOI: 10.1073/pnas.0236364100
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of activation by phosphoinositides determines lipid regulation of Kir channels

Abstract: Phosphoinositides are critical regulators of ion channel and transporter activity. Defects in interactions of inwardly rectifying potassium (Kir) channels with phosphoinositides lead to disease. ATP-sensitive K ؉ channels (KATP) are unique among Kir channels in that they serve as metabolic sensors, inhibited by ATP while stimulated by long-chain (LC) acyl-CoA. Here we show that KATP are the least specific Kir channels in their activation by phosphoinositides and we demonstrate that LC acyl-CoA activation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
234
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(243 citation statements)
references
References 37 publications
9
234
0
Order By: Relevance
“…These results suggest that anchoring of the C terminus to the membrane occurs via a nonspecific electrostatic interaction to phosphoinositide (36) of the post-M4 polybasic motif and not to specific binding of PI(4,5)P2. Such nonspecific binding is reminiscent of the MARKS effector domain (33) and GIRK and K ATP channels (37,38) and differs from the stereo-specific PI(4,5)P2-selective interaction of the IRK1 channel and of the plextrin homology domain of PLC (36). Such nonspecific charge interaction is consistent with TREK1 channel regulation by anionic phospholipids in the inner leaflet lipid and not by cationic lipids (8).…”
Section: Discussionsupporting
confidence: 53%
“…These results suggest that anchoring of the C terminus to the membrane occurs via a nonspecific electrostatic interaction to phosphoinositide (36) of the post-M4 polybasic motif and not to specific binding of PI(4,5)P2. Such nonspecific binding is reminiscent of the MARKS effector domain (33) and GIRK and K ATP channels (37,38) and differs from the stereo-specific PI(4,5)P2-selective interaction of the IRK1 channel and of the plextrin homology domain of PLC (36). Such nonspecific charge interaction is consistent with TREK1 channel regulation by anionic phospholipids in the inner leaflet lipid and not by cationic lipids (8).…”
Section: Discussionsupporting
confidence: 53%
“…Many members of the Kir (inwardly-rectifying K ϩ channel) family of K ϩ channels are regulated by G protein-coupled receptors that alter the P o over short time frames through phosphatidylinositol bisphosphate metabolism or protein-protein interactions (18,19). We found that co-expression of the CaR WT and Kir4.1 in Xenopus oocytes led to reduced whole cell currents, whereas the nonfunctional mutant CaR R795W had no effect (10).…”
Section: Control Of Kir41 Cell Surface Abundance By Car-mentioning
confidence: 77%
“…These results indicate that the effects of the CaR on Kir4.1 are distinct from the conventional effects of G␣ q -coupled receptors that involve short term regulation of second messengers such as inositol 1,4,5-trisphosphate or phosphatidylinositol bisphosphate, kinases such as PKC, or protein-protein interactions that occur over seconds. Instead, they depend on protein trafficking that occurs over a time scale of a few to many minutes (10,19).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PIP 2 directly modulates the activity of ion channels and transporters ( Hilgemann and Ball, 1996 ;Fan and Makielski, 1997 ;Runnels et al, 2002 ;Roh á cs et al, 2003 ;Chemin et al, 2005 ;Suh and Hille 2005 ;Brauchi et al, 2007 ;Hilgemann, 2007 ;Roh á cs 2007 ;Voets and Nilius, 2007 ). In spite of the key roles of PIP 2 and BK channels in cell excitability and signaling, it remains unknown whether PIP 2 can directly modulate BK channel function.…”
Section: Excised Patch Recordings From Vascular Myocytesmentioning
confidence: 99%